2004
DOI: 10.1074/jbc.m309789200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Autoregulatory Feedback Pathway Involving Interleukin-1α in Induction of Constitutive NF-κB Activation in Pancreatic Cancer Cells

Abstract: We previously reported that NF-B is constitutively activated in most human pancreatic cancer tissues and cell lines but not in normal pancreatic tissues and immortalized pancreatic ductal epithelial cells. IB␣M-mediated inhibition of constitutive NF-B activity in human pancreatic cancer cells suppressed tumorigenesis and liver metastasis in an orthotopic nude mouse model, suggesting that constitutive NF-B activation plays an important role in pancreatic tumor progression and metastasis. However, the underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 49 publications
3
81
0
Order By: Relevance
“…This is what we found with two antimelanoma CTL clones, including a CTL recognizing the immunodominant peptide Melan-A/MART1 [26][27][28][29][30][31][32][33][34][35] , presented by HLA-A2. In a previous study, IFN-c was shown to reduce by up to 78% the cytotoxicity of anti-Melan-A/MART-1 26-35 CTL, despite the stimulatory effect of IFN-c on MHC class I expression and antigen presentation.…”
Section: Tumor Immunologysupporting
confidence: 74%
See 1 more Smart Citation
“…This is what we found with two antimelanoma CTL clones, including a CTL recognizing the immunodominant peptide Melan-A/MART1 [26][27][28][29][30][31][32][33][34][35] , presented by HLA-A2. In a previous study, IFN-c was shown to reduce by up to 78% the cytotoxicity of anti-Melan-A/MART-1 26-35 CTL, despite the stimulatory effect of IFN-c on MHC class I expression and antigen presentation.…”
Section: Tumor Immunologysupporting
confidence: 74%
“…In a previous study, IFN-c was shown to reduce by up to 78% the cytotoxicity of anti-Melan-A/MART-1 26-35 CTL, despite the stimulatory effect of IFN-c on MHC class I expression and antigen presentation. 22 This reduction is most likely due to the induction of the immunoproteasome, which does not process the Melan-A/MART-1 [26][27][28][29][30][31][32][33][34][35] peptide. 42 Data of a recent study suggest that IL-1b is not able to induce the immunoproteasome.…”
Section: Tumor Immunologymentioning
confidence: 99%
“…Mechanisms of NF-kB activation in pancreatic cancer appear to involve K-Ras and Akt activation, as well as Notch-1 signaling, nuclear glycogen synthase kinase-3b, and Vav1 (Wang et al, 1999c(Wang et al, , 2006Asano et al, 2004;Fernandez-Zapico et al, 2005;Ougolkov et al, 2005). Additionally, it has been reported that autocrine production of IL-1a regulates NF-kB activation in pancreatic cancer cells (Niu et al, 2004). NF-kB-regulated gene targets that encode proteins potentially relevant to the maintenance and invasion of pancreatic cancer cells are proposed to be GADD45a and urokinase-type plasminogen activator (Wang et al, 1999b;Schneider et al, 2006).…”
Section: Nf-kb and Pancreatic Cancermentioning
confidence: 99%
“…We have previously reported that elevated secretion of certain growth factors can cause constitutive NF-B activation in many cancer cell lines, and probably, also in tumors (13,14). Others have reported that Ap1 causes elevated growth factor secretion and the ensuing activation of NF-B which, in turn, cooperates with Ap1 (25). In that case, however, the cycle only partially depended on NF-B because its inhibition failed to curtail Ap-1 activity.…”
Section: Discussionmentioning
confidence: 97%